NMR Spectroscopic Studies of Intrinsically Disordered Proteins at Near‐Physiological Conditions1. Issue 45 (20th September 2013) - Gil, Sergio; Hošek, Tomáš; Solyom, Zsofia; Kümmerle, Rainer; Brutscher, Bernhard; Pierattelli, Roberta; Felli, Isabella C.
<x xml:space="preserve">Abstract</x> When approaching physiological conditions, solvent exchange of amide protons in intrinsically disordered proteins (IDPs) is so pronounced that it becomes a key feature to be considered in NMR experiment design. 13C NMR experiments recover information that is not accessible through amide proton detection, and solvent exchange can be used to increase sensitivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>